2022
DOI: 10.1182/bloodadvances.2021005246
|View full text |Cite|
|
Sign up to set email alerts
|

C5a and C5aR1 are key drivers of microvascular platelet aggregation in clinical entities spanning from aHUS to COVID-19

Abstract: Unrestrained activation of the complement system till the terminal products, C5a and C5b-9, plays a pathogenetic role in acute and chronic inflammatory diseases. In endothelial cells, complement hyperactivation may translate into cell dysfunction, favoring thrombus formation. The aim of this study was to investigate the role of the C5a/C5aR1 axis as opposite to C5b-9 in inducing endothelial dysfunction and loss of anti-thrombogenic properties. In vitro and ex vivo assays with serum from patients with atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…There is evidence that C3a and C5a, generated following complement activation, are driving factors in altering endothelial thromboresistance ( 59 , 84 , 85 ). Further proof-of-concept that C5a has thrombogenic effects on endothelial cells comes from data showing that C5a inhibition halts the platelet aggregation induced by sera from severe COVID-19 patients, possibly through the exocytosis of vWF and P-selectin ( 48 ). Finally, data from the UK show that genetic predisposition to complement dysregulation is a risk factors for morbidity and death from SARS-CoV-2 infection, which indicates that hyperactivation of complement is a hallmark feature of the pathophysiology of severe COVID-19 ( 86 , 87 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that C3a and C5a, generated following complement activation, are driving factors in altering endothelial thromboresistance ( 59 , 84 , 85 ). Further proof-of-concept that C5a has thrombogenic effects on endothelial cells comes from data showing that C5a inhibition halts the platelet aggregation induced by sera from severe COVID-19 patients, possibly through the exocytosis of vWF and P-selectin ( 48 ). Finally, data from the UK show that genetic predisposition to complement dysregulation is a risk factors for morbidity and death from SARS-CoV-2 infection, which indicates that hyperactivation of complement is a hallmark feature of the pathophysiology of severe COVID-19 ( 86 , 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that S1 can directly activate the alternative pathway of complement on the cell surface by interfering with Factor H function ( 47 ). Lastly, our group recently documented that exposing sera from severe COVID-19 patients to endothelial cells induced platelet aggregation via the engagement of C5a/C5aR1 axis ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…BK generated by the KK system activation can cause dry cough ( 74 ) and pulmonary inflammation with edema ( 75 ) by binding to BKR2. C3a and C5a bind to the anaphylatoxin receptors: C3aR, C5aR1, and C5aR2 and C5a is also able to activate endothelial cells in COVID-19 patients leading to von Willebrand Factor (vWF) and p-selectin exposure on the endothelial lining thereby contributing to the thrombotic phenotype ( 76 ). Supporting the importance of the C5a/C5aR1 axis is that COVID-19 patients generate C5a as detected in pulmonary lavage in proportion to the severity of the disease and high expression of C5aR1 was found in blood and on pulmonary myeloid cells ( 77 ).…”
Section: Conceptual Mechanisms Inducing Covid-19-triggered Ardsmentioning
confidence: 99%
“…Aiello et al. reported that C3 and C5b-9 deposits obtained after a single healthy subject serum (N=12) incubation range from 0.5 to 1.5 fold increase of stained surface area compared to pooled serum (from 10 healthy donors) run in parallel ( 87 ).…”
Section: Study Of Complement Deposition On Cultured Endothelial Cellsmentioning
confidence: 99%